Genetic variability of Indonesian Oryctes rhinoceros nudivirus (OrNV) as genus of Alphanudivirus - Sat Rahayuwati; Yayi Munara Kusumah; Sudharto Prawirosukarto; Dadang; Teguh Santoso (Society for Indonesian Biodiversity, 2020)
Abstract. Rahayuwati S, Kusumah YM, Prawirosukarto S, Dadang, Santoso T. 2020. Genetic variability of Indonesian Oryctes rhinoceros nudivirus (OrNV) as genus of Alphanudivirus. Biodiversitas 21: 2047-2055. Oryctes rhinoceros nudivirus (OrNV) is known as a successful classical biological control agent. Recent reports have revealed differences in pathogenicity among OrNV isolates, with correlation suspected between virus virulence and genetic variability. The aim of the research is to study the genetic variability of OrNV isolates based on the DNA polymerase (DNA pol) gene and their phylogenetic relationship with Genus Alphanudivirus. Oryctes rhinoceros (Coleoptera: Scarabaeidae) as an OrNV host were collected from Sumatra, Belitung, Java, Kalimantan, and Sulawesi. Primers were designed to amplify complete gene of DNA pol. Sequencing, phylogenetic, and investigate genetic diversity scores were used to determine variability at nucleotide level. Five primers successfully amplified the entire DNA pol gene. Genetic variability of OrNV was high, from nine isolates found eight genetically different. Isolates could be divided into two groups of genetic diversity: high and low. High genetic diversity of OrNV supposed as an old population that occupied Sundaland and Wallacean paleogeography at first appearance in Miocene Era until early Pliocene 5 Mya. New population of OrNV had low genetic diversity were travel cross-island that supposed to correlate with oil palm plantation development and the genetic drift. The benefit information of the OrNV genetic variability is as preliminary guideline for virulence test. OrNV is a member of Nudiviridae family, Genus Alphanudivirus, and at recent moment they consist of eight species. Alphanudivirus infect Coleoptera, Diptera, Hemiptera and Orthoptera order that soil as immature niche may explain their closely related taxa.